2017
DOI: 10.1371/journal.pone.0172859
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the instrument of health literacy competencies for Chinese-speaking health professionals

Abstract: The study aimed to illustrate the constructs and test the psychometric properties of an instrument of health literacy competencies (IOHLC) for health professionals. A multi-phase questionnaire development method was used to develop the scale. The categorization of the knowledge and practice domains achieved consensus through a modified Delphi process. To reduce the number of items, the 92-item IOHLC was psychometrically evaluated through internal consistency, Rasch modeling, and two-stage factor analysis. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The assessment of the need for social support, the educative attitude and attitudes that make patients co-responsible in the educational process were differentials of our study in relation to other lists of HCP competences in HL. Previous studies have suggested that HL theoretical knowledge is an important competency, including concepts, definitions and guidelines [16,17,24]. Em contraponto, o conhecimento teo ´rico do HL não foi priorizado pelos nossos especialistas refletindo uma proposta pra ´tica para os itens de competência.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of the need for social support, the educative attitude and attitudes that make patients co-responsible in the educational process were differentials of our study in relation to other lists of HCP competences in HL. Previous studies have suggested that HL theoretical knowledge is an important competency, including concepts, definitions and guidelines [16,17,24]. Em contraponto, o conhecimento teo ´rico do HL não foi priorizado pelos nossos especialistas refletindo uma proposta pra ´tica para os itens de competência.…”
Section: Discussionmentioning
confidence: 99%
“…We considered experts in health literacy to be professionals who had at least six months of experience in a care activity that involved carrying out educational activities with the patient. This time of experience in care can be considered minimal to allow the opportunity to experience HL practices, as shown by the result of a previous study [24].…”
Section: Interviews With Healthcare Professionalsmentioning
confidence: 99%
“…In contrast, the English version of the Instrument Of Health Literacy Competencies (IOHLC) developed by Taiwanese scholar Li‐Chun Chang for medical staff includes specific content that medical staff should design lesson plans for patients with low health literacy, simple and specific teaching, creating a friendly environment, using simple and easy‐to‐use materials, life‐oriented teaching, checking patients' understanding, encouraging patients to ask questions, designing materials for patients' self‐direction and interdisciplinary collaboration. The model fits well, with Cronbach's alphas >0.80, and can be used to comprehensively and validly assess the health literacy competencies of medical professionals (Chang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that, because health literacy has a variety of definitions and structures, researchers have designed different tools for measuring health literacy in different groups, and each tool measures one aspect of health literacy. A number of known tools include oral health literacy [13], adolescent health literacy [14], health literacy in women with breast cancer [15], health literacy in people with chronic diseases such as diabetes [16,17], Asthma [18] and hypertension [19], health literacy competencies [20], scale of low salt consumption [21], and weight literacy scale [22]. Abel (2014) states that, examining health literacy in different domains requires different research approaches [23].…”
Section: Introductionmentioning
confidence: 99%